The Prince Lobkowitz Palace in Vienna. Augustine Church and Cloister - Prixner, Gottfried, 1746-1819 (engraver):::Creator::::::::::::; Weidmann, F.C. (Franz Carl), 1787-1867 (author):::Contributor:::::::::::: (Vienna; R. Sammer, Buchhändler beym Kärtherthore, 2020)
Engraving of the Lobkowitz Palace and Augustine Church and Cloister in Vienna, with 2 pages of explanatory text in German.